Communication and Linguistic Competences for Middle Management: A Content Analysis of Job Advertisements - Mariana CERNICOVA-BUCĂ (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages, 2020)
The paper analyzes the provisions regarding communication and linguistic skills, excerpted from job advertisements recruiting middle management leaders in Romania. Through a qualitative content analysis, this study approaches organizational requirement information to better understand the communication and linguistic competence description of the ideal candidate in industrial settings. Scholars, teachers, and practitioners need to constantly check the transformations and requirements on the labor market and showcase the competences developed by educational programs, especially of master’s degree programs. The key contribution of this paper is the presentation of “soft skills” in job advertisements, bridging the gap between academia and labor market expectations.